The Government of Uganda adopts PIM recommendations to improve a nationwide program aimed at involving citizens towards effective public service delivery - CGIAR Research Program on Policies, Institutions, and Markets (2020)
PIM researchers conducted an impact evaluation of the Baraza program, which has been implemented by the Office of the Prime Minister since 2009 to improve public services. The findings and recommendations of the study are being used to increase the program’s cost-effectiveness and inclusivity, potentially affecting millions of citizens throughout the country.